Some aspects of construction of the enterprises rating estimations - Kravets, Tetyana (Publishing House of the Wrocław University of Economics, 2009)
The research problems of economic inequality both between different systems and between elements of the same type (subsystems) of one system are emerging under study of economic processes. Research of an economic inequality leads to necessity of transition from a set of the indicators characterizing a subsystem, to one numerical characteristic – to a rating. In developed countries independent experts that are helping to take economic decisions are rating agencies, which build the rating system of different economic objects, and rating space, structured by regional and sector indication. Receiving by an industrial enterprise the rating of an international agency is necessary if it is going to expand the foreign financial markets or to attract foreign investors. Procedure of receiving the rating assumes audit of financial activity under the international standards of book keeping, competitiveness of production in the world market, presence of modern system of management and transparency of activity of the enterprise. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 253-259